Route to tunable room temperature electric polarization in SrTiO3–CoFe2O4 heterostructures. Issue 18 (26th April 2021) - Maurel, Laura; Herrero-Martín, Javier; Motti, Federico; Vasili, Hari Babu; Piamonteze, Cinthia; Heyderman, Laura J.; Scagnoli, Valerio
Abstract : We show reversible room temperature control of the Ti band structure in SrTiO3 –CoFe2 O4 heterostructures exploiting CoFe2 O4 magnetostriction. Changes as a function of the applied magnetic field suggest the development of a net electric polarization. Abstract : Utilizing the magnetostrictive properties of CoFe2 O4, we demonstrate reversible room temperature control of the Ti electronic structure in SrTiO3 –CoFe2 O4 heterostructures, by inducing local and reversible strain in the SrTiO3 . By means of X-ray absorption spectroscopy, we have ascertained the changes that take place in the energy levels of the Ti 3d orbitals under the influence of an external magnetic field. The observed Ti electronic state when the sample is subjected to moderately large external magnetic fields and the disappearance of the induced phase upon their removal indicates lattice distortions that are suggestive of the development of a net electric polarization.